(untitled) (Research, Society and Development, 2023)
The development of the nervous system involves a series of processes and interactions between the external and internal environment, genes and experiences. Primary care tools and assessments are needed as a routine part of maternity hospitals, and they need to be quick and easy to apply. This article aims to investigate whether neonates who show warning signs in neurological development have difficulty breastfeeding. In view of this, a quantitative, observational cross-sectional study was carried out using the Hammersmith Neonatal Neurological Examination (HNNE) for neurological screening and the LATCH instrument to assess the quality of breastfeeding, in a sample of 58 newborns between 24 and 48 hours postpartum. The HNNE and the LATCH are assessment instruments that are easy and quick to use, freely accessible and, therefore, a promising option to be used in primary care in Brazil. The profile of the babies was mostly, male (60%), full-term (38 weeks) and with Apgar within the normal range in the first (78%) and fifth (96.3%) minute. However, the results did not show a significant association between difficulty in breastfeeding and warning signs for neurological development in full-term and low-risk neonates.